Abusive Language: Viewed from Early Childhood Social Environment Behavior - Amanda, Elvina; Romlah, Romlah (Jurnal Pendidikan Amartha, 2025)
In the process of early childhood development, one of the demanding aspects of development is language. The phenomenon of increasingly uncontrolled development of abusive language is a negative impact of language development. This negative impact has spread to early childhood in the form of verbal violence against children. The aim of this research is to determine the impact of children's behavior that often speaks harshly. This research is qualitative research using a descriptive approach. The research results show that young children do not yet have a special filter to determine whether the language they will use in building communication with other people is good or bad so they can easily imitate the behavior of their social environment. The role of parents in supervising and providing support in their children's social environment can reduce the level of children's exposure to abusive language.